What is the impact of Impatiens parviflora on diversity and composition of herbal layer communities of temperate forests? - Hejda, Martin (PLoS One, 2012)
The aim was to estimate the impacts of invasive Impatiens parviflora on forests' herbal layer communities. A replicated Before-After-Control-Impact field experiment and comparisons with adjacent uninvaded plots were used. The alien's impact on species richness was tested using hierarchical generalized mixed effect models with Poisson error structure. Impact on species composition was tested using multivariate models (DCA, CCA, RDA) and Monte-Carlo permutation tests. Removal plots did not differ in native species richness from neither invaded nor adjacent uninvaded plots, both when the treatment's main effect or its interaction with sampling time was tested (Chi(2) = 0.4757, DF = 2, p = 0.7883; Chi(2) = 7.229, DF = 8, p = 0.5121 respectively). On the contrary, ordination models revealed differences in the development of plots following the treatments (p = 0.034) with the invaded plots differing from the adjacent uninvaded (p = 0.002). Impatiens parviflora is highly unlikely to impact native species richness of invaded communities, which may be associated with its limited ability to create a dense canopy, a modest root system or the fact the I. parviflora does not represent a novel and distinctive dominant to the invaded communities. Concerning its potential impacts on species composition, the presence of native clonal species (Athyrium filix-femina, Dryopteris filix-mas, Fragaria moschata, Luzula luzuloides, Poa nemoralis) on the adjacent uninvaded plots likely makes them different from the invaded plots. However, these competitive and strong species are more likely to prevent the invasion of I. parviflora on the adjacent uninvaded plots rather than being themselves eliminated from the invaded communities.
Keywords: Czech Republic; Trees; Models, Biological; Česká republika; Impatiens; Species Specificity; Biota; společenstvo; stromy; druhová specificita; biologické modely